Photosynthesis, water relations and growth of young coffee plants according to phosphorus availability - da Silva, Leandro; Marchiori, Paulo Eduardo Ribeiro; Maciel, Cíntia Pinheiro; Machado, Eduardo Caruso; Ribeiro, Rafael Vasconcelos (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate how high soil phosphorus (P) availability affects the photosynthesis and growth of young coffee arabica plants (Coffea arabica). Four months old coffee seedlings of the Ouro Verde cultivar, cultivated in good hydric conditions, were exposed to three P availability treatments: P dosage recommended in the literature (RP); two times the recommended dosage (P+); and without P (P-). Seventy days after treatment application, evaluations of leaf gas exchange, photochemical activity, leaf water potential, plant hydraulic conductance (KL), dry matter partitioning, leaf contents of pigments and carbohydrates, and leaf chemical composition were done. The treatment without P caused reduction in photosynthesis, leading to lower plant growth. The plants of the P+ treatment showed the highest leaf P concentrations ( 1.9 g kg-1), with increasing leaf CO2 assimilation and instantaneous carboxylation efficiency, and higher photochemical activity – higher effective quantum efficiency of photosystem II and apparent electron transport rate – when compared to plants exposed to RP treatment. Plants exposed to the double P recommended dosage exhibited higher KL, higher leaf carbohydrate content and higher chlorophyll content, resulting in higher dry matter production as compared to RP and P-.